2020
DOI: 10.13057/biodiv/d211119
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric hybrids of Phalaenopsis 2166 x Vanda ‘Saint Valentine’ showing maternal inheritance: Genetic analysis based on ndhE partial gene

Abstract: Abstract. Dwiati M, Susanto AH, Prayoga L. 2020. Intergeneric hybrids of Phalaenopsis 2166 x Vanda ‘Saint Valentine’ showing maternal inheritance: Genetic analysis based on ndhE partial gene. Biodiversitas 21: 5138-5145. Genetic characterization in the intergeneric hybridization of orchids employing a particular molecular marker, such as ndhE gene, is needed to avoid phenotypic plasticity. The hybridization between Phalaenopsis 2166 as a female parent and Vanda ‘Saint Valentine'as a male parent has been succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Six sults suggested that interspecific hybridization can contribute to increase the genetic variation of Dendrobium section Spatulata. Another study reported that hybridization between two different species produced high variation in all progenies of orchid (Dwiati et al 2020).…”
Section: Flower Morphology Of Parental and Progeny Lines Of Antelope ...mentioning
confidence: 99%
“…Six sults suggested that interspecific hybridization can contribute to increase the genetic variation of Dendrobium section Spatulata. Another study reported that hybridization between two different species produced high variation in all progenies of orchid (Dwiati et al 2020).…”
Section: Flower Morphology Of Parental and Progeny Lines Of Antelope ...mentioning
confidence: 99%
“…The other three hybrids, i.e., F1.9, F1.11, and F1.14, showed slightly different ndhE sequences from that of Phalaenopsis 2166, and they have also been registered in the NCBI database as MH646651. One of the three hybrids, i.e., F1.14, has a partially spotted reddish-purple leaf that is predictable to produce conspicuously attractive flowers, thus potentially to be developed into a large number of plant individuals (Dwiati et al 2020b;Dwiati and Susanto 2021).…”
Section: Introductionmentioning
confidence: 99%